COVID-19 and hematopoietic stem cell transplantation: recommendations from the Brazilian Society of Bone Marrow Transplantation (SBTMO) - Machado, Clarisse Martins (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Abstract The beginning of 2020 was marked by the rapid spread of SARS CoV-2 worldwide, causing the pandemic of COVID-19, which has represented a major public health problem. HSCT centers must be prepared to deal with the difficulties imposed by the pandemic. This manuscript summarizes some of the knowledge acquired so far regarding SARS CoV-2 and COVID-19, and the main recommendations for HSCT centers.